2022
DOI: 10.3390/nu14142839
|View full text |Cite
|
Sign up to set email alerts
|

Acute Beetroot Juice Supplementation Enhances Intermittent Running Performance but Does Not Reduce Oxygen Cost of Exercise among Recreational Adults

Abstract: Nitrate (NO3−) supplementation has been reported to enhance intermittent exercise performance; however, its impact on oxygen (O2) cost during intermittent running exercise is unclear. The aim of this study was to assess if acute NO3− supplementation would elicit performance benefits in recreationally active individuals during the Yo–Yo intermittent recovery level 1 (Yo-Yo IR1) test, with its potential benefit on O2 consumption (VO2), in a double-blind, randomized, crossover study, 12 recreational males consume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(30 citation statements)
references
References 50 publications
0
27
1
Order By: Relevance
“…Acute supplementation of BRJ did not provide a significant effect on the prone Yo‐Yo IR1 test performance in the present study. This finding is in contrast to recent reports that BRJ supplementation improved the total distance covered in the standard Yo‐Yo IR1 test in recreational and trained participants (Wylie et al, 2013; Thompson et al, 2016; Nyakayiru et al, 2017; Esen et al, 2022b). Mostly based on those previous studies above, NO 3 ‐ supplementation is suggested as an ergogenic aid for improving team sport performance.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Acute supplementation of BRJ did not provide a significant effect on the prone Yo‐Yo IR1 test performance in the present study. This finding is in contrast to recent reports that BRJ supplementation improved the total distance covered in the standard Yo‐Yo IR1 test in recreational and trained participants (Wylie et al, 2013; Thompson et al, 2016; Nyakayiru et al, 2017; Esen et al, 2022b). Mostly based on those previous studies above, NO 3 ‐ supplementation is suggested as an ergogenic aid for improving team sport performance.…”
Section: Discussioncontrasting
confidence: 99%
“…The Yo‐Yo intermittent recovery level 1 test (Yo‐Yo IR1) is well‐established, ecologically valid and commonly used (Krustrup et al, 2003) and heretofore, recent studies have shown an enhanced performance in the Yo‐Yo IR1 test following varied supplementation regimen of NO 3 ‐ (range of dose between 6.4 and 29 mmol; and range of duration between acute and 7‐days supplementation) in various populations (i.e. active adults, recreational or/and trained soccer, hockey players) (Wylie et al, 2013; Thompson et al, 2016; Nyakayiru et al, 2017; Esen et al, 2022b). Although these studies have concluded that NO 3 ‐ supplementation might be an ergogenic aid for team sport athletes, translation of these findings to every team sport activity and/or players is complicated due to the considerable differences in technical requirements and metabolic demand of each team sport.…”
Section: Introductionmentioning
confidence: 99%
“…The dose, duration, and type of NO 3 − supplementation varied between studies. NO 3 − supplementation was administered as beetroot juice (n = 24) [34][35][36][37][38][39][40][41]51,[53][54][55][56][57][58][60][61][62][63][64][65][66]74,75], potassium NO 3 − (n = 1) [59], pomegranate extract (n = 1) [67], or as a high NO 3…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Seven studies had a low risk of bias in the randomisation process [34,36,39,54,59,63,67] and the remaining twenty studies had some concerns [35,37,38,40,41,[51][52][53][55][56][57][58][60][61][62][64][65][66]74,75]. All studies had a low risk of bias for bias arising from period and carryover effects [34][35][36][37][38][39][40][41][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65]…”
Section: Quality Assessmentmentioning
confidence: 99%
“…Existing literature shows that nitrate supplementation may enhance muscle contractility, particularly peak power and time to peak power [72]. There is also evidence that nitrate supplementation enhanced intermittent exercise performance [73,74], sprint performance, and cognitive performance (i.e., reaction time) [75] in recreationally active individuals and trained team-sport athletes. There are a couple of important points to consider when applying nitrate supplementation.…”
Section: Nitrate/beetroot Juicementioning
confidence: 99%